Coleophora gecidiella Baldizzone, sp. n., a new species from Turkey. The female of Coleophora turca Baldizzone, 1994. Contribution to the knowledge of the Coleophoridae CLI (Lepidoptera: Coleophoridae) - Giorgio Baldizzone (SHILAP, 2022)
Coleophora gecidiella Baldizzone, sp. n., new species from Turkey belonging to the group of C. onobrychiella Zeller, 1849 is described based on specimens collected by Günther Baisch. The female of C. turca Baldizzone, 1994, a species of which only the male is known, is described for the first time.